E-learning in dental schools in the times of COVID-19 : a review and analysis of an educational resource in times of the COVID-19 pandemic = E-learning en las escuelas de odontología en los tiempos de COVID-19 : Una revisión y análisis de un recurso educativo en tiempos de la pandemia de COVID-19 - Chavarría Bolaños, Daniel 1982-; Gómez Fernández, Adrián José 1980-; Dittel Jiménez, Carmen Eugenia 1965-; Montero Aguilar, Mauricio 1978- (2020)
While countries are facing different stages in their COVID-19 infection rates, worldwide there are millions of students affected by universities' facilities closures due to the pandemic. Some institutions have enforced strategies to transfer some courses to a virtual modality, but many Dental Schools have been challenged to deal with a situation which requires emergency measures to continue the academic course in the middle of lock-downs and social distancing measures. Despite the fact that the number of online academic programs available, especially graduate programs, has increased in diverse modalities, this pandemic forced e-learning processes to develop abruptly. The likelihood of using e-learning strategies in dentistry was substantiated in the scientific literature and an overview of these opportunities is presented. Additionally, the experience of the University of Costa Rica Faculty of Dentistry is presented, as it was evident that some of the key elements in a e-learning environment needed a quick enhancement and initiation of some processes was required. First, it was necessary to categorize the academic courses depending on their virtualization's possibility (curricula analysis and classification), to better understand the extent of the impact and the work needed to contain, as far as the possibilities allowed, negative consequences on students learning process. Second, teachers needed further training in the application of virtual strategies which they hadn't used before. do Third, an evaluation of the students' conditions and needs was conducted in a form of a survey. Finally, teachers and students activated the available virtual platforms. For many Dental Schools, this virtualization process is an ongoing progress although it was abruptly imposed, but this moment indeed represents an enormous opportunity to move forward and get immerse in the virtualization environment as a teaching/learning experience.
Mientras muchos países están enfrentando distintas etapas en sus tasas de contagio de COVID-19, millones de estudiantes alrededor del mundo han sido afectados por el cierre de instalaciones universitarias debido a la pandemia. Algunas instituciones han aplicado estrategias para transferir algunos cursos a una modalidad virtual, pero muchas facultades de odontología se han visto enfrentadas a una situación que requiere medidas de emergencia para continuar el curso académico en medio de bloqueos y medidas de distanciamiento social. A pesar de que el número de programas académicos en línea disponibles, especialmente los programas de postgrado, ha aumentado en diversas modalidades, esta pandemia obligó a desarrollar abruptamente los procesos de aprendizaje electrónico. La probabilidad de utilizar estrategias de aprendizaje electrónico en odontología se vió corroborada en la literatura científica y se presenta una visión general de estas oportunidades. Además, se presenta la experiencia de la Facultad de Odontología de la Universidad de Costa Rica, ya que fue evidente que algunos de los elementos clave en un entorno de aprendizaje electrónico necesitaban una rápida mejora y se requería la iniciación de algunos procesos. En primer lugar, era necesario clasificar los cursos académicos en función de las posibilidades de su virtualización (análisis y clasificación de los planes de estudio), para comprender mejor el alcance de las repercusiones y la labor necesaria para contener, en la medida de las posibilidades, las consecuencias negativas en el proceso de aprendizaje de los estudiantes. En segundo lugar, los profesores necesitaban más capacitación en la aplicación de estrategias virtuales que no habían utilizado antes. En tercer lugar, se realizó una evaluación de las condiciones y necesidades de los estudiantes en forma de encuesta. Finalmente, los profesores y estudiantes activaron las plataformas virtuales disponibles...
En revista Odóvtos, vol. 22, no. 3 (septiembre-diciembre 2020)
Descripción basada en el contenido visto el 10 de octubre, 2024
También disponible en formato HTML y EPUB